Cytotoxic Lymphocytes Target HIV-1 Gag Through Granzyme M-Mediated Cleavage - Saccon, Elisa; Mikaeloff, Flora; Figueras Ivern, Pol; Végvári, Ákos; Sönnerborg, Anders; Neogi, Ujjwal; van Domselaar, Robert (Frontiers in Immunology, 2021)
HIV-1 leads to progression to immunodeficiency and death of individuals who do not receive successful antiretroviral therapy. Initially, the host’s immune response controls the infection, but cannot eliminate the HIV-1 from the host. Cytotoxic lymphocytes are the key effector cells in this response and can mediate crucial antiviral responses through the release of a set of proteases called granzymes towards HIV-1-infected cells. However, little is known about the immunological molecular mechanisms by which granzymes could control HIV-1. Since we noted that HIV-1 subtype C (HIV-1C) Gag with the tetrapeptide insertion PYKE contains a putative granzyme M (GrM) cleavage site (KEPL) that overlaps with the PYKE insertion, we analyzed the proteolytic activity of GrM towards Gag. Immunoblot analysis showed that GrM could cleave Gag proteins from HIV-1B and variants from HIV-1C of which the Gag-PYKE variant was cleaved with extremely high efficiency. The main cleavage site was directly after the insertion after leucine residue 483. GrM-mediated cleavage of Gag was also observed in co-cultures using cytotoxic lymphocytes as effector cells and this cleavage could be inhibited by a GrM inhibitor peptide. Altogether, our data indicate towards a noncytotoxic immunological mechanism by which GrM-positive cytotoxic lymphocytes target the HIV-1 Gag protein within infected cells to potentially control HIV-1 infection. This mechanism could be exploited in new therapeutic strategies to treat HIV-1-infected patients to improve immunological control of the infection.